2005
DOI: 10.1038/sj.onc.1208940
|View full text |Cite
|
Sign up to set email alerts
|

Selenoprotein deficiency and high levels of selenium compounds can effectively inhibit hepatocarcinogenesis in transgenic mice

Abstract: The micronutrient element selenium (Se) has been shown to be effective in reducing the incidence of cancer in animal models and human clinical trials. Selenoproteins and low molecular weight Se compounds were implicated in the chemopreventive effect, but specific mechanisms are not clear. We examined the role of Se and selenoproteins in liver tumor formation in TGFa/c-Myc transgenic mice, which are characterized by disrupted redox homeostasis and develop liver cancer by 6 months of age. In these mice, both Se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
79
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 38 publications
9
79
0
1
Order By: Relevance
“…On the other hand, it was recently shown that selenium deficiency caused cell death due to accumulation of reactive oxygen species, especially lipid peroxides (47). This effect probably explains the results of Novoselov et al showing antihepatocarcinogenic effect in a transgenic mouse model both at high levels of selenium and at selenium deficiency but not at intermediate selenium levels (12). Interestingly, most hepatocellular carcinoma cell lines tolerate selenium deficiency probably as a result of selection for survival in oxidative stress -induced selenium-deficient conditions (48).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…On the other hand, it was recently shown that selenium deficiency caused cell death due to accumulation of reactive oxygen species, especially lipid peroxides (47). This effect probably explains the results of Novoselov et al showing antihepatocarcinogenic effect in a transgenic mouse model both at high levels of selenium and at selenium deficiency but not at intermediate selenium levels (12). Interestingly, most hepatocellular carcinoma cell lines tolerate selenium deficiency probably as a result of selection for survival in oxidative stress -induced selenium-deficient conditions (48).…”
Section: Discussionsupporting
confidence: 54%
“…Chemoprevention against hepatocellular carcinoma in mouse models has previously been achieved with antioxidants, including vitamin E (10), tannic acid (13), and some selenium compounds (11,12). In most cases, the chemopreventive agent was supplemented during several months, but in some models, a short prenatal and postnatal exposure resulted in significant decrease of hepatocellular carcinoma incidence (11).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of Sep15 is also subject to regulation by dietary Se, and it belongs to the group of stress-related selenoproteins. However, in some organs, including brain and testis, the decrease in Sep15 expression under Se-deficient conditions is less pronounced (99,267). Interestingly, there are two polymorphic sites at nucleotide positions 811 (C/T) and 1125 (A/G) in the human Sep15 gene (192).…”
Section: H the 15-kda Selenoprotein And Selenoprotein Mmentioning
confidence: 99%
“…Finally, MsrB1 is a nonessential selenoprotein (106), whose expression is regulated by Se availability (267). Moreover, expression of this selenoprotein is reduced in mice as a function of age (269).…”
Section: Methionine-r-sulfoxide Reductasementioning
confidence: 99%
“…In contrast, expression of other selenoproteins, such as GPx1, is rather sensitive towards selenium shortage and their expression is quickly downregulated when selenium becomes limiting. This peculiarity of selenoprotein biology suggests that high-ranking selenoproteins may play a more essential role in the organism (Novoselov et al, 2005). Although the underlying mechanism of selenoprotein expression hierarchy is not fully elucidated, mRNA stability has been proposed as a regulation level (Weiss-Sachdev and Sunde, 2001;Muller et al, 2003).…”
Section: Introductionmentioning
confidence: 99%